Widowhood Rituals among Some Ethnic Groups Africa - Dorgbetor, Alfred (Future Science / FSH-PH Publications, 2021)
Widowhood rites are widely believed to be practices that a bereaved spouse must undergo upon becoming a widow in many parts of the world. It is the time period during which a woman transitions from being a wife to being a widow in her family and community. Different societies associate widowhood with a variety of different customs and values, which have a significant impact on how it is experienced. This article therefore sought to examine the practice among some Ethnic groups in Ghana and some African countries.